أزمة الهوية وعلاقتها بتقدير الذات لدى المراهقين المتمدرسين بمرحلة الثانوي - حنكة، نجاة (جامعة الوادي university of Eloued, 2019)
الملخص: هدفت هذه الدراسة إلى الكشف عن العلاقة بين أزمة الهوية وتقدير الذات لدى عينة من التلاميذ المتمدرسين في بعض ثانويات الوادي, والتعرف كذلك على مستويات تقدير الذات وأزمة الهوية لدى هذه العينة. ولتحقيق الهدف المرجو تم اتباع المنهج الوصفي لأنه أكثر ملائمة لطبيعة هذه الدراسة التي نحن بصددانجازها, وطبقت الدراسة على عينة قوامها(100)تلميذ وتلميذةمن بعض ثانويات الوادي تم اختيارهم بطريقة عشوائية عرضية. وتم جمع البيانات وتبويبها ومعالجتها، وذلك بعد استخدام المقياسين تقدير الذات لكوبر سميث النسخة المصغرة ومقياس ازمة الهويةلدكتور فاضل خليل إبراهيم والدكتور يوسف حنا. وللتحقق من فرضيات الدراسة تم استخدام الأساليب الإحصائية التالية: - معامل الارتباط بيرسون لحساب العلاقة بين ازمة الهوية وتقديرالذات. - ختبار T.test - اختباركا² وكانت نتائج الدراسة كالآتي : - يتميز أغلبية المراهقين المتمدرسين بمستوى أزمة هوية مرتفع. - يتميز أغلبية المراهقين المتمدرسين بمستوى تقدير الذات معتدل. - لا توجد علاقة بين أزمة الهوية ومستوى تقدير الذات لدى المراهقين المتمدرسين في المرحلة الثانوية ببعض ثانويات ولاية الوادي. Résumé : انجلزية The aim of this study was to uncover the relationship between identity crisis and self-esteem among a sample of students who were educated in some of the secondary levels in El-Oued. Also, to identify the levels of self-esteem and identity crisis in this sample. To achieve the desired goal, the descriptive approach was followed because it is more appropriate to the nature of this study. The study was applied to a sample of (100) students from some of the secondary schools in El-Oued randomly chosen. The data were collected, tabulated and processed after the use of the self-assessment test of Cooper Smith and the identity crisis test by Dr. Fadel Khalil Ibrahim and Dr. Yousef Hanna. To verify the hypothesis of the study, the following statistical methods were used Pearson correlation coefficient to calculate the relationship between identity crisis and self - esteem. - T test - K² test The results of the study were as follows: - The majority of educated adolescents are characterized by a high identity crisis. - The majority of educated adolescents do not have a moderate level of self-esteem. - There is no relationship between the identity crisis and the level of self-esteem among adolescents who are taught in the secondary stage in some of the secondary levels of the valle
دراسة ميدانية على عينة من المراهقين المتمدرسين ببعض ثانويات ولاية الوادي
مذكرة ماستر في علوم التربية تخصص إرشاد وتوجيه
Keywords: أزمة الهوية، تقدير الذات; Crise d'identité, estime de soi; Identity crisis, self-esteem